(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
The increasing pollution of the environment due to textile dye effluents in Nigeria is a major source ofdanger to both aquatic environment and human health thus there is need to have sustainable remediationmeasures. This paper explores synthesis and analysis of iron-doped clay-based nanomaterials using thelocal resources in Ogun State, Nigeria to degrade popular textile dyes, reaction to Congo Red andMethylene Blue. Sampling was done in three locations- Ijebu-Ode, Abeokuta and Ifo characterized byX-ray diffraction and scanning electron microscopy which showed the predominating mineral askaolinite with different percentages of quartz and illite. Nanomaterials were prepared through wetimpregnation using the iron chloride and then underwent calcination at 500 C which improvedresponsiveness of the material to visible light. The efficiencies of degradation of the two dyes in alaboratory-scale reactor (with LED irradiation of less than 100 W) at 4 hours showed efficiencies higherthan 75 percent of each dye following pseudo-first-order kinetics, with rate constants of 0.015 to 0.025min -1. Reusability tests indicated that it was stable after five cycles with more than 60% of efficiency.The study incorporates primary primary data in form of batch experiments done in triplicate andstatistical analysis of ANOVA, which supports the idea of significant differences between performanceaccording to clay source and doping level. The localized solutions are made in local areas, and the needto utilize these solutions is justified by the demographic factors of Ogun State being mainly Yorubaethnic groups with a population of about 6.38 million who carry out their agricultural and industryactivities. The results are in favor of scaling these nanomaterials in the treatment of wastewater toprovide cost-effective alternatives to the existing one. The work contributes to the environmentalchemistry field since the use of indigenous resources to control pollution in developing situations isutilized.